The Algorithmic Gaze: Deconstructing Authorship and Aesthetics in Generative Artificial Intelligence (AI) Art - Hesti Putri; Dais Susilo; Ervin Munandar; Hanifah Yasin; Idris Atmaja (Enigma Institute, 2025)
The proliferation of advanced text-to-image generative AI represents a paradigmatic shift in visual culture. It instigates a profound crisis for established concepts of authorship and aesthetics while also raising critical questions about artistic labor and the political economy of cultural production. This study investigates the complex negotiations between human creators and algorithmic systems. This study employed a qualitative, multi-modal methodology. A visual semiotic analysis was conducted on a curated corpus of 300 artworks from Midjourney, DALL-E 3, and Stable Diffusion, sampled to mitigate platform-specific biases. This was triangulated with a thematic analysis of semi-structured interviews with a purposive sample of 15 artists and designers actively using these tools. The methodological limitations, specifically the sample's